(untitled) (Journal of Pakistan Orthopaedic Association, 2013)
Background: Femoral shaft fractures are common in adult population due to vulnerability to road traffic accident and firearm injuries. The Gamma nail was introduced for the treatment of subtrochanteric fractures with the theoretical advantage of a load-sharing femoral component which could be implanted by a closed procedure. Gamma nails were implanted with significantly shorter operating times, smaller incsions, and less intraoperative bleeding. Objective: To determine the outcome of Gamma nail in complex subtrochanteric femur fractures in terms of clinicoradiological evidence of union. Study Design: Descriptive case series. Setting: Department of Orthopaedics and Spinal Surgery, Ghurki Trust Teaching Hospital/Lahore Medical & Dental College, Lahore. Duration of Study with Dates: One Year (1st November, 2010 to 31st, 2011). Methods: After evaluation according to Advance Trauma Life Support (ATLS) protocol, 50 cases of subtrochanteric femur fractures were included. Gamma nail of appropriate size and angle was introduced with help of jig. Proximal lag screw fixation was done. Patients were mobilized on first postoperative day with help of crutches or walker. Full weight bearing was allowed within six weeks. Clinical evidence of bone healing was scored according to pain and mobility scale. Results: There were 20 males and 30 females. Male to female ratio was 1:1.5. The mean±SD between the ages was 42.24±13.76 years. There were 36 closed procedures and 14 open procedures done in all patients. The outcome of Gamma nails in complex subtrochanteric femur fractures were 43 patients having union and 7 patients have non-union. Conclusion: Gamma nail is an alternative treatment of choice for complex subtrochanteric femur fractures. It allows the patients to get out of bed early and good rates of union.